Investigation the Influence of Green Brand Knowledge and Attitude towards Green Brands on Purchase Intention Corkcicle: The Mediating Role of Brand Equity - Udayanti, Imel; Madiawati, Putu Nina; Widodo, Arry (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores how Green Brand Knowledge and Attitude Toward Green Brand influence Purchase Intention, with Brand Equity acting as a mediating variable. The research is contextualized within Corkcicle, an eco-friendly lifestyle tumbler brand, and targets environmentally conscious Gen Z consumers. A quantitative approach was employed using Structural Equation Modeling (SEM-PLS). Data were collected from 300 Gen Z respondents in Bandung, Indonesia, who are familiar with Corkcicle through social media and online platforms. The findings indicate that both Green Brand Knowledge and Attitude Toward Green Brand significantly and positively influence Purchase Intention. Furthermore, Brand Equity plays a significant mediating role in this relationship, reinforcing its importance in green brand strategies. These results suggest that sustainability-oriented branding, particularly when supported by strong brand equity, can effectively drive green purchase intention among younger consumers. The study contributes to green marketing literature by validating the mediating role of Brand Equity and offers practical insights for brands aiming to foster eco-friendly buying behavior through digital engagement and value-based branding.